A knowledge-based theory of the firm: nexus of intellectual capital, productivity and firms’ performance - Kengatharan, N. (Emerald Publishing Limited, 2019)
Purpose Drawing on the knowledge-based theory of the firm, the study examines the relationship between each facet of intellectual capital, productivity and firms’ performance and further investigates, heretofore neglected, a mediating effect of productivity in the relationship between each facet of intellectual capital and firms’ performance. Design/methodology/approach Data were garnered with a self-reported questionnaire from 232 firm managers working in various industries: banking, insurance, telecommunications and hotels. Reliability and validity of the instruments were confirmed using confirmatory factor analysis. Prior to hypothesis testing using structural equation modelling, as a caveat, tests for nonresponse bias and common method variance were employed. Findings The study confirmed that intellectual capital is the pièce de résistance and established a strong connection with productivity. The results further disclosed a positive relationship between productivity and firms’ performance. A mediated relationship between individual facets of intellectual capital and firms’ performance through productivity was also affirmed. Practical implications Chiefly, the study underscored the importance of intellectual capital in promoting productivity and firms’ performance. It behoves human resource managers and practitioners to make the organisational arrangements to reinforce intellectual capital thereby boosting the productivity that brings organisations success. Originality/value Previous studies in the sphere of intellectual capital have unequivocally discounted in establishing relationships between intellectual capital, productivity and firms’ performance. The results of the study are novel findings, unequivocally contributing to the frontiers of the knowledge-based theory of the firm and conjointly, the study has made methodological and geographical contributions.
Keywords: Firms’ performance; Industries; Intellectual capital; Knowledge-based theory of the firm; Productivity